2004
DOI: 10.1007/978-3-642-18756-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Metastability, conformation dynamics, and transition pathways in complex systems

Abstract: Summary. We present a systematic introduction to the basic concepts and techniques for determining transition pathways and transition rates in systems with multiple metastable states. After discussing the classical transition state theory and its limitations, we derive a new set of equations for the optimal dividing surfaces. We then discuss transition path sampling, which is the most general technique currently available for determining transition regions and rates. This is followed by a discussion on minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In the latter context, the ability to account for directionality and history is critical – particularly tracing back any given trajectory to the most recently occupied state (A or B, “initial” or “target” state), which enables unbiased rate calculation [*11,12,13]; see also [14,15]. This insight from path theory has important practical implications for analyzing ordinary MD simulations and avoiding the Markov assumption [16].…”
Section: Path Sampling Methods and Recent Advancesmentioning
confidence: 99%
“…In the latter context, the ability to account for directionality and history is critical – particularly tracing back any given trajectory to the most recently occupied state (A or B, “initial” or “target” state), which enables unbiased rate calculation [*11,12,13]; see also [14,15]. This insight from path theory has important practical implications for analyzing ordinary MD simulations and avoiding the Markov assumption [16].…”
Section: Path Sampling Methods and Recent Advancesmentioning
confidence: 99%
“…Recently the interest in MSMs has drastically increased since it could be demonstrated that MSMs can be constructed even for very high dimensional systems [73] and have been especially useful for modeling the interesting slow dynamics of biomolecules [56,57,58,12,11,61] and materials [79] (there under the name "kinetic Monte Carlo"). Their approximation quality on large time scale has been rigorously studied, e.g., for Brownian or Glauber dynamics and Ising models in the limit of vanishing smallness parameters (noise intensity, temperature) where the analysis can be based on large deviation estimates and variational principles [29,84] and/or potential theory and capacities [8,9]. In these cases the effective dynamics is governed by some MSM with exponentially small transition probabilities and its states label the different attractors of the underlying, unperturbed dynamical systems.…”
Section: Standard Markov State Modelsmentioning
confidence: 99%
“…Particularly in molecular dynamics, MSM have become popular as approximations of the conformational dynamics [72,73,84] of large biomolecules, which exhibits various timescales ranging from protein folding to fast vibrations and oscillations within a molecular conformation. There, the subdivision of the conformational state space has been usually achieved by partitioning [56,11,15,35,39,60,64,52,71,80,81].…”
Section: Introductionmentioning
confidence: 99%
“…The approximation quality of a MSM on large time scales has been rigorously studied for many different systems, e.g., for diffusion processes, or Glauber dynamics and Ising models in the limit of vanishing smallness parameters (noise itensity, temperature) where the analysis can be based on large deviation estimates and variational principles [21,22] and/or potential theory and capacities [23,24]. In these cases the effective dynamics is governed by some MSM with exponentially small transition probabilities and its states label the different attracting sets of the underlying Markov process.…”
Section: Introductionmentioning
confidence: 99%